What it takes to become a physician scientist in a low- and middle-income country. - Beatriz Barreto-Duarte; Simon C Mendelsohn; Elsa Du Bruyn; Bruno B Andrade (PLOS Global Public Health)
Physician-scientists, who have dual medical and advanced research training, are a scarce and valuable asset. They bridge clinical practice and research, address critical medical challenges with a scientific perspective, and drive innovation by translating discoveries into patient care. Physicians with research expertise are particularly adept at critically evaluating scientific literature to improve their practice and ensure that they provide up-to-date, individualised, and evidence-based care to their patients. However, the path to becoming a physician-scientist in Low- and Middle-Income Countries (LMICs) is fraught with challenges. In this article, we explore the difficulties faced by physician-scientists in LMICs, including lengthy and arduous training, systems that favour eminence-based over evidence-based medicine, and financial disincentives for pursuing a dual career in medicine and research. The article also highlights the significant underrepresentation of women in medical and scientific fields, compounded by gender-specific challenges such as balancing motherhood with career demands, gender pay gaps, and the lack of supportive and affirmative policies. We advocate for reforms in medical education to create a more supportive environment for aspiring physician-scientists. Addressing these issues can help LMICs enhance the contribution of physician-scientists to global health and scientific advancement.